Age at menarche and risk of vasomotor menopausal symptoms: a pooled analysis of six studies. (21st July 2020) - Chung, H‐F; Zhu, D; Dobson, AJ; Kuh, D; Gold, EB; Crawford, SL; Avis, NE; Mitchell, ES; Woods, NF; Anderson, DJ; Mishra, GD
Abstract : Objective: To examine the association between age at menarche and risk of vasomotor menopausal symptoms (VMS) and whether midlife body mass index (BMI) modified the association. Design: A pooled analysis of six cohort studies. Setting: The International collaboration on the Life course Approach to reproductive health and Chronic disease Events (InterLACE). Population: 18 555 women from the UK, USA and Australia. Methods: VMS frequency data (never, rarely, sometimes and often) were harmonised from two studies ( n  = 13 602); severity data (never, mild, moderate and severe) from the other four studies ( n  = 4953). Multinominal logistic regression models were used to estimate relative risk ratios (RRRs) and 95% CIs adjusted for confounders and incorporated study as random effects. Main outcome measures: Hot flushes and night sweats. Results: Frequency data showed that early menarche ≤11 years was associated with an increased risk of 'often' hot flushes (RRR 1.48, 95% CI 1.24–1.76) and night sweats (RRR 1.59, 95% CI 1.49–1.70) compared with menarche at ≥14 years. Severity data showed similar results, but appeared less conclusive, with RRRs of 1.16 (95% CI 0.94–1.42) and 1.27 (95% CI 1.01–1.58) for 'severe' hot flushes and night sweats, respectively. BMI significantly modified the association as the risk associated with early menarche and 'often' VMS was stronger among women who were overweight or obese than those of normal weight, while this gradient across BMI categories was not as strong with the risk of 'severe' VMS. Conclusions: Early age at menarche is a risk factor for VMS, particularly for frequent VMS, but midlife BMI may play an important role in modifying this risk. Tweetable abstract: Overweight and obesity exacerbate the risk of vasomotor symptoms associated with early menarche. Tweetable abstract: Overweight and obesity exacerbate the risk of vasomotor symptoms associated with early menarche.